PasoDoble, a Proposed Dance/Music for People With Parkinson's Disease and Their Caregivers - Giménez-Llort, Lydia; Castillo-Mariqueo, Lidia (Frontiers in Neurology, 2020)
Managing the heterogeneity of Parkinson’s disease symptoms and its progressive nature demands strategies targeting the hallmark disrupted neurotransmission but also the comorbid derangements and bolstering of neuroprotection and regeneration. Strong efforts are done to find disease-modifying strategies, since slowing disease progression is not enough to hamper its burden and some motor symptoms are resistant to dopamine-replacement therapy. The inclusion of non-pharmacological strategies can provide such a multitarget umbrella approach. The silent long-term biological process that precedes the clinical onset of disease is a challenge but also an opportunity to reinforce healthy lifestyle known to exert preventive/therapeutic effects. These non-pharmacological strategies are foreseen as able to reduce the prevalence and the global impact of long-term diseases demanding strong management of patient-caregiver quality of life. In this regard, European guidelines for Parkinson’s disease recommend physical-related activities such as aerobic exercise and dancing known to improve functional mobility and balance in patients. Here, we propose 'PasoDoble', a novel dance/music patient-caregiver intervention with additional preventive value. The rationale is founded on evidence-based therapeutic benefits of dance/music therapy and the singular features of this widely extended Hispanic dance/music targeting motor symptoms, mood/cognition and socialization: i) As a dance, an easy and simple double-step pattern (back-and-forward and lateral movements) that evolves from a spontaneous individual dance to a partnered dancing, performed in social groups and involving dancing-figures of increasing complexity; ii) PasoDoble, as a music that can be sung, has musical rhythmicity with high groove and familiarity that will help to synchronize the steps to the rhythm of music; iii) Widely extended (Spain, Mexico, Puerto Rico, Colombia and USA) and easy-to-learn for others. As a regular dancing ‘PasoDoble’ can improve and preserve function, mood and socialization, as an intervention the method is structured to improve gait and balance; facilitate movement, reaching and grasping; muscle power and joint mobility; reduce of risk of falls, and increase of aerobic capacity. Finally, this easy-to-implement into patient care and free-living environments (elderly social centers, home) rehabilitation program can promote positive emotions and self-esteem, with added general improvement of social attachment and recognition, thus improving the quality of life of patient-caregiver.